QoS evaluation of different TCPs congestion control algorithm using NS2 - Tarmizi, M.; Albagul, A.; Khalifa, Othman Omran; Wahyudi, Martono (2006)
The success of the current Internet relies to a large extent on cooperation between the users and network. The network signals its current state to the users by marking or dropping packets. The user then strives to maximize the sending rate without causing network congestion. To achieve this, the users implement a flow control algorithm that controls the rate at which data packets are sent into the Internet. More specifically, the Transmission Control Protocol (TCP) is used by the users to adjust the sending rate in response to changing network conditions. In this paper, we focus on the degree of fairness provided to TCP connections by comparing two packet-scheduling algorithms at the router. The first one is FIFO (First In First Out, or Drop-Tail), which is widely used in the current Internet routers because of its simplicity. The second is RED (Random Early Detection), which drops incoming packets at a certain probability.